تأثير بعض تدريبات الربط الحركي على أداء مهارة الإستلام و التمرير بالقدم المفضلة و الغير مفضلة - الجندي، ثروت محمد محمد; جادو، محمد عبدالعزيز; بارود، عماد أحمد (جامعة المنصورة - كلية التربية الرياضية, 2014)
إن مشكلة البحث تتلخص بأن الغالبية العظمى من لاعبي كرة يعتمدون اعتماد كلي على القدم المفضلة وحدها في أداء المهارات الأساسية في كرة القدم مما قد يحصر خياراتهم في تنفيذ واجباتهم المهارية والخططية في مواقف اللعب المختلفة إذا ما واجههم موقف يحتم عليهم استخدام القدم المفضلة في الأداء، وتم اختيار مهارة الاستلام والتمرير نظرا إلي إنها المهارة الأكثر استخدام في الملعب وخصوصا لدي الناشئين في كرة القدم، ويهدف البحث إلي التعرف على تأثير تدريبات الربط الحركي على أداء مهارة الاستلام والتمرير بالقدم المفضلة والغير مفضلة، واستهدف البحث مجموعة عشوائية من ناشئين كرة القدم تحت سن 14 سنة من نادي العمال، واتخذ البحث المنهاج التجريبي لمناسبته لتحقيق أهداف البحث، وجاءت نتائج الدراسة بصورة إيجابية تفيد بوجود فروق ذات دلالة إحصائية بين القياسين القبلي و البعدي لصالح القياس البعدي في متغير القدرة على الربط الحركي وفي متغير مهارة الاستلام والتمرير في كرة القدم، حيث أظهرت النتائج حدوث تحسن في مستوى أداء مهارة الاستلام والتمرير لدي عينة، وجاءت نتائج التحسن متباينة بين كل من القدم المفضلة والقدم الغير مفضلة، ويرجع الباحث هذا التحسن إلى التدريبات الخاصة بتنمية القدرة على الربط الحركي داخل البرنامج التدريبي المقترح والذي تم تنفيذه بواقع 3 وحدات تدريبية في الأسبوع لمدة ثلاثة اشهر متتالية، وكانت التوصيات الخاصة بالبحث تحث على أهمية إجراء دراسات وأبحاث مشابهة لهذه الدراسة وتعتنى بباقي القدرات التوافقية وتقيس مدى تأثيرها على باقي المهارات الأساسية في كرة القدم، هذا كله بغرض تعزيز دور البحث العلمي في إثراء حقل التدريب والتدريس في مجال التربية الرياضية وخصوصا فيما يتعلق بكرة قدم الناشئين. The research problem is summed up that the vast majority of football players rely adopt entirely on foot favorite alone in the performance of basic skills in football , which may limit the choices in the implementation of their duties of skill and tactical in the positions of different play if confronted with the position of having them use football favorite performance was choosing the skill of receipt and scrolling as they endure the most use in the field and especially I have a junior in football , and the research aims to identify the impact of training connectivity motor on the performance of the skill of pick-up and scroll -footed favorite and non- favorite , and targeted research group at random from junior football under the age of 14 years Club workers , and took the search platform demo for its relevance to achieve the goals of the research, the results of the study are positive indicating that there is statistically significant differences between the two measurements tribal and posttest for the benefit of dimensional measurement in a variable ability to link motor in variable skill receiving and passing in football , where the results showed an improvement in the level of performance of the skill of the receipt and scrolling in a sample , and the results came improvement differentiated between each of the foot favorite football non- favorite , due researcher of this improvement to the exercises on the development of the ability to link the motor within the proposed training program which was implemented by 3 training units per week for three consecutive months , and the recommendations for research urges the importance of conducting studies and research similar to this study and take care of the rest of the capacity harmonic and measure its impact on the rest of the basic skills in football , that's the whole purpose of strengthening the role of scientific research in enriching the field of training and teaching in the field of physical education and especially with respect of a football rookies .
Keywords: كرة القدم -- التدريب الرياضي -- اللاعبون -- المهارات الرياضية